Табір інтернованих військ УНР у Вадовицях, Польща: умови перебування та моральний стан вояцтва в травні-липні 1921 р. - Срібняк, І. (Міжнародні зв’язки України: наукові пошуки і знахідки, 2017)
У статті проаналізовано умови перебування та моральний стан
інтернованого українського вояцтва в таборі Вадовиці (Польща).
Доведено, що побут вояків-українців був позначений значними труднощами, зумовленими його перенаселеністю й доволі жорстким режимом утримання інтернованих. Також мало місце неприхильне, недоброзичливе, навіть вороже ставлення до інтернованих вояків-українців з
боку окремих службовців комендатури табору. Все це призводило до
деморалізації тієї частини інтернованого українського вояцтва, яке не
мало стійких національно-державницьких почувань. У цих умовах конче
необхідним було зміцнити моральний дух таборян, чим опікувались
культурно-освітні відділи дивізій, таборовий театр та інші культурно-мистецькі осередки. Значну гуманітарну допомогу інтернованим надавала таборова філія YMCA. The article analyzes the conditions of stay and morale of the interned
Ukrainian army in the Wadowice camp (Poland). It was proved that the life of
Ukrainian soldiers was marked by considerable difficulties due to overcrowding
of the camp, a rather tight regime of keeping interned, limiting the
ability to temporarily leave the camp, the unpreparedness of the camp
commandant’s office to go to a meeting with the interned in solving their most
pressing problems.
Ukrainian soldiers’ ration was reduced, and sometimes they received
spoiled products; they were devoid of soap; the camp still had a group of
captive Red Army soldiers with Bolshevik agitators in their environment; there
was a prohibition of singing songs (outside the camp, while studying, etc.). All
this was aggravated by malevolence and even hostility to interned Ukrainian
soldiers on the part of the individual officers of the camp (sometimes even
offensive attitude to them), the intrusion of the camp’s commandant into the
internal life of Ukrainian soldiers.
All this led to the demoralization of the part of the interned Ukrainian
army, which did not have stable national-state feelings. One of its manifestations
was the desertion of several dozen interned from the camp, including
officers. In these conditions, it was imperative to consolidate the moral spirit of
the interned, what the cultural-educational departments were cared for. In
order to create positive values, actors-amateurs of the camp’s theater regularly
offered warriors performances by Ukrainian playwrights. The YMCA
camp branch, which, despite the anti-Ukrainian position of its head, objectively
changed the lives of the interned for the better.